The Implications of Energy Input Flexibility for a Resource Dependent Economy - Karen Pittel; Luise Röpke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The paper analyzes resource policies in an economy in which renewable and fossil resources are realistically assumed to be essential inputs to production. Also realistically, the two types of resources are imperfect substitutes whose degree of substitutability can, however, increase over time. The focus of the - analytical as well as numerical - analysis is on the impact of this rising substitutability on the extraction of the exhaustible resource. This is especially interesting in a setting in which the use of the fossil resource induces a market failure, e.g., in the form of an environmental externality (of which climate change is the most prominent example), and in which policies are introduced to internalize this market failure. It is shown that policies which aim to slow down resource extraction but whose design is determined from political rather than optimality considerations are likely to result in even faster resource extraction. We show that this effect - often labeled a Green Paradox - can be accompanied by extraction-increasing effects of rising substitutability. More specifically, we find two types of flexibility effects that have opposing effects on the extraction path. The first effect speeds up extraction due to the expectation of higher flexibility in the future. This effect arises independently of whether the increase in substitutability is due to exogenous technological change or is endogenously driven. The second effect slows down extraction and arises when substitutability increases endogenously in accord with a changing input mix. Our results have several important implications for the design of policy measures. Specifically, a policy measure that induces flexibility-increasing technological progress must take into consideration the supply-side effects that result from the anticipation of increasing flexibility. The model also shows that for a policy to be effective, not only must flexibility effects be taken into account but the specific type of flexibility effect is also important.
Keywords: Q32; O44; O30; 330